Organizational involvement, academic procrastination, and emotional exhaustion in college students - Peristianto, Sheilla Varadhila; Widyana, Rahma (Universitas Mercu Buana Yogyakarta, 2025)
Student activists are actively engaged in organizational activities both within and beyond their university. While such involvement offers benefits such as enhanced social skills and personal development, it can also have negative consequences, including tardiness or absenteeism in classes, a decline in academic performance, and difficulties in completing assignments on time. One manifestation of these challenges is academic procrastination. This study aims to examine the relationship between organizational involvement and academic procrastination, with emotional exhaustion as a mediating variable among college students. The study sample comprised 80 student activists in Yogyakarta, selected using a purposive sampling method. Using path analysis with bootstrapping (1,000 resamples) in IBM® SPSS® AMOS™ 21, the findings reveal a significant mediating effect of emotional exhaustion on the relationship between organizational involvement and academic procrastination. The results indicate that the duration of organizational involvement is associated with higher levels of academic procrastination, mediated by emotional exhaustion. These findings highlight the need for universities to implement programs that help students balance organizational engagement with academic responsibilities, thereby reducing emotional exhaustion and mitigating procrastination. Keyword: Academic procrastination, duration of organizational involvement, emotional exhaustion, organizational activity.